Calculati:
Răspunsuri la întrebare
Răspuns de
7
Răspuns:
Explicație pas cu pas:
a) (√3 + √5·x)²-(√15·x-2)²=(√3)²+2·√3·√5·x+(√5·x)² - [(√15·x)²-2·√15·x·2+2²] = 3+2·√15·x+5x²-(15x²-4√15·x+4)=3+2·√15·x+5x²-15x²+4√15·x-4=
=-10x²+6√15·x-1;
b) ... = 3²-2·3·√14·x+(√14·x)² - [(√7·x)²+2·√7·x·√2+(√2)²]=9-6√14·x+14x² -7x²-2√14·x-2=7x²-8√14·x+7;
c) ... = (2√2·x)²-2·2√2·x·√3+(√3)²+(√2)²+2·√2·2√3·x+(2√3·x)²=
=8x²-4√6·x+3+2+4√6·x+12x²=20x²+5;
d) ... = (√5·x)²+2·√5·x·4√2+(4√2)²-[(3√2·x)²-2·3√2·x·√5+(√5)²]=
=5x²+8√10·x+32-(18x²-6√10·x+5)=5x²+8√10·x+32-18x²+6√10·x-5=
= -13x²+14√10·x+27.
Alte întrebări interesante